THE ASSOCIATION OF EXAGGERATED EXERCISE AND 24H BLOOD PRESSURE WITH LEFT VENTRICULAR HYPERTROPHY IN NORMOTENSIVE MEN AND WOMEN ADJUSTED FOR CARDIORESPIRATORY FITNESS. (June 2018) - Pittaras, A.; Kokkinos, P.; Doumas, M.; Narayan, P.; Grassos, H.; Kallistratos, M.; Papavasiliou, M.; Kouremenos, L.; Kyfnidis, K.; Poulimenos, L.; Pyriovoli, G.; Manolis, A.J.; et al.
Abstract : Objective: Left ventricular hypertrophy (LVH) increases the risk of cardiac events. Exercise blood pressure (BP) and ambulatory BP (ABPM) are associated with LVH, while cardiorespiratory fitness (CRF) is associated with lower BP at absolute workloads. This suggests that abnormally elevated BP during daily activities may be the stimulus for LVH. Thus, we assessed the association between exercise BP, ABPM and LVH in normotensive individuals based on office BP. Design and method: We assessed cardiac structure and function, ABPM, and CRF in 1, 022 normotensive men (n = 697; age: 51 ± 10) and women (n = 325; age: 54 ± 10), not treated by any medications. Results: LVH was present in 24.7% with women having approximately 3 times higher prevalence (14.9% vs 45.5%). The strongest predictors of LVH were the increase in SBP from resting to exercise at Bruce I (5 METs), (OR = 1.17; p < 0.001); the difference between resting and SBP at 3 min of exercise (OR = 1.17; p < 0.001, and daytime ABPM (OR = 1.16; p < 0.001). There was also a 44% reduction in the risk for LVH for every 1 MET increase in the workload (OR: 0.56; P < 0.001). Cut-off analysis revealed a threshold for LVH > 150mmHg for SBP at 5 METs and 15 mm Hg increase beyond resting BP at Stage I and 140 mm Hg for daytime SBP. The LVH risk increased by approximately 5-fold for every 10 mm Hg increases beyond these thresholds. To account for the impact of CRF on LVH, we stratified the cohort into age-specific fitness quartiles and compared cardiac parameters (Table). Figure. No caption available. Conclusions: Systolic BP response during workloads of approximately 5 METs provides the stimulus for increased left ventricular mass and LVH. CRF attenuates the BP response and the development of LVH.